Trapped in the Net : the Unanticipated Consequences of Computerization. - Rochlin, Gene I. (Princeton University Press, 2001)
Voice mail. E-mail. Bar codes. Desktops. Laptops. Networks. The Web. In this exciting book, Gene Rochlin takes a closer look at how these familiar and pervasive productions of computerization have become embedded in all our lives, forcing us to narrow the scope of our choices, our modes of control, and our experiences with the real world. Drawing on fascinating narratives from fields that range from military command, air traffic control, and international fund transfers to library cataloging and supermarket checkouts, Rochlin shows that we are rapidly making irreversible and at times harmful c.